Pulmonary function and systolic blood pressure in very low birth weight infants at 34–36 weeks of corrected age - Gievers LL; Jenkins RD; Laird A; Macedo MC; Schilling D; McEvoy CT (Dove Medical Press, 2019)
Ladawna L Gievers,1 Randall D Jenkins,1 Amy Laird,2 Marissa C Macedo,1 Diane Schilling,1 Cindy T McEvoy1 1Department of Pediatrics, Oregon Health and Science University, Portland, OR, USA; 2Division of Biostatistics, School of Public Health, Oregon Health and Science University, Portland, OR, USACorrespondence: Ladawna L GieversDepartment of Pediatrics, Oregon Health and Science University, 707 SW Gaines Road, Portland, OR 97239, USATel +1 503 494 1077Fax +1 503 494 1542Email gievers@ohsu.eduPurpose: Preterm infants are at increased risk of systemic hypertension compared to term infants. Bronchopulmonary dysplasia (BPD) has been shown to be associated with hypertension in preterm infants albeit with no causation reported. BPD is characterized by abnormal pulmonary function tests (PFTs), specifically elevated passive respiratory resistance (Rrs), decreased passive respiratory compliance (Crs), and decreased functional residual capacity (FRC). There have been no studies comparing PFTs in very low birth weight (VLBW) infants with and without hypertension. We hypothesized that stable VLBW infants with hypertension will have altered PFTs.Patients and methods: Retrospective cohort study of infants <1500 g at birth (VLBW) who had PFTs performed near 34–36 weeks of corrected gestational age (CGA). We excluded infants with congenital anomalies, known hypertensive disorders or those at risk of medication-induced hypertension. Data obtained included PFT parameters (Rrs, Crs, FRC) and mean systolic blood pressure (SBP).Results: Fifty-nine VLBW infants were identified for analysis, 14 with and 45 without hypertension. Hypertensive and normotensive patients were similar in terms of mean gestational age (26.6 vs 27.4 weeks), mean CGA at PFTs (36.1 vs 34.6 weeks) and proportion of BPD (36% vs 36%). The Rrs was significantly higher in hypertensive versus normotensive patients [median Rrs of 0.080 (0.069, 0.090) versus 0.066 (0.054, 0.083) cmH2O/mL/s; p=0.04]. There was no difference in systolic blood pressure in the infants with and without BPD.Conclusion: In this cohort of contemporary VLBW infants, those with hypertension had increased Rrs. This finding warrants a prospective study with a larger sample size and long-term follow-up.Keywords: hypertension, bronchopulmonary dysplasia, pulmonary function test, neonate